Analysis of Labor Productivity at the Pottery Craft Industry Center in Masbagik Timur Village, Masbagik District, East Lombok Regency - Majdi, Ahmad; Daeng, Akung; Handayani, Tuti (Westscience Press, 2025)
This study is entitled